Plasticity periods effects in second language acquisition and speech behaviour profiles: the age factor and decoding skills changing. - Figueiredo, Sandra (2018)
The age factor always is considered above other factors, by most research, evidencing the children as the true experts in the acquisition of L2, which is becoming seriously a controversy. Will be discussed results regarding the general decoding competence and the phonological awareness and consciousness. The results may suggest that the different ages in the speech perception and production apply to different strategies, discussing the theoretical of the critical period for the languages acquisition.